KEARIFAN LOKAL LEI MASELEN SEBAGAI MITIGASI SOSIAL DAN PENYAKIT DI NEGERI LAIMU - Almaskaty, Saiful Ali; Huliselan, Mus; Watloly, Aholiab; Leiwakabessy, Jeffry EM (FISIP Universitas Malikussaleh, 2024)
The aim of the research is to strengthen the Laimu community's strategy in maintaining the local wisdom of Lei Maselen so that it does not become extinct due to developments over time. This research specifically also aims to be a mitigation strategy for social problems and diseases in Laimu Village, Telutih sub-district, Central Maluku district. Linguistically, Lei means to drive away, while Maselen means disease, so in case of its terms, Lei Maselen is a ritual of expulsion or an effort to mitigate disease outbreaks. This tradition is the community's effort to maintain the continuity of life, while maintaining the relationship with the creator. The local wisdom of the Laimu people has been going on for hundreds of years, and the process of inheritance takes place orally. To obtain accurate and valid data, researchers used qualitative research with a field-study projects. Data obtained at the research location was gained through four strategies, such as involving the author in community social activities, conducting structured interviews with the community, main informants and supporters, carrying out field notes to anticipate data not being recorded, and carrying out documentation. After the data was collected, the researcher carried out analysis using qualitative data analysis procedures. Including data reduction, presenting data, interpreting data, and drawing conclusions.